Evaluation the Effectiveness of Capital Expenditure for Well Construction at The PUPR Department of East Nusa Tenggara Province - Mooy, Angelia Febrianti; Perseveranda, M. E.; Baso, Susana Purnamasari (AKSIOMA : Jurnal Manajemen, 2025)
This study focuses on the low infrastructure index and Human Development Index (HDI) in East Nusa Tenggara (NTT), indicating an urgent need for access to clean water. The objective of the research is to evaluate the effectiveness of capital expenditure by the Public Works and Housing Office (PUPR) of NTT Province in the development of borewell infrastructure. Data were collected through interviews and official documents, including budget realization reports and project package lists. The results indicate that the budget allocation for borewell construction is significant and close to the budget ceiling, reflecting the local government’s commitment. The financial effectiveness of capital expenditure is very good, with most projects rated as "very successful." However, the physical achievement of the construction has only reached 90.43%, leaving a gap of 9.57% from the target. Factors affecting effectiveness include delays in implementation and geographical conditions. The study concludes that the management of capital expenditure is effective, but attention is needed to achieve optimal physical targets.